No Better Time to Practice Open Science Than Now - Akligoh, Harry (My University, 2020)
This is a guest speaker presentation given at the virtual Open Science Fellows Program 2020 in Berlin. The presentation captures the speakers perspectives on Open Science where he related it to the story of William Kamkwamba from Malawi, his journey through Open Science and Projects and Initiatives that are making use of Open Science in overcoming the challenges of COVID-19 today.
Keywords: Africa; COVID-19; Open Science